Me and the boss : a story about mending and love - Edwards, Michelle (Anne Schwartz Books, 2022)
Six-year-old Lee will not give up until he can show his big sister Zora, a.k.a. the boss, how good he can sew. Includes instructions on how to make Lee's smiling moon.